Opium use and risk of lung cancer: A multicenter case‐control study in Iran. Issue 2 (31st August 2022) - Rashidian, Hamideh; Hadji, Maryam; Gholipour, Mahin; Naghibzadeh‐Tahami, Ahmad; Marzban, Maryam; Mohebbi, Elham; Safari‐Faramani, Roya; Bakhshi, Mahdieh; Sadat Seyyedsalehi, Monireh; Hosseini, Bayan; Alizadeh‐Navaei, Reza; Emami, Habib; et al.
Abstract: Opium use was recently classified as a human carcinogen for lung cancer by the International Agency for Research on Cancer. We conducted a large, multicenter case‐control study evaluating the association between opium use and the risk of lung cancer. We recruited 627 cases and 3477 controls from May 2017 to July 2020. We used unconditional logistic regression analyses to estimate the odds ratios (OR) and 95% confidence intervals (CI) and measured the association between opium use and the risk of lung cancer. The ORs were adjusted for the residential place, age, gender, socioeconomic status, cigarettes, and water pipe smoking. We found a 3.6‐fold risk of lung cancer for regular opium users compared to never users (95% CI: 2.9, 4.6). There was a strong dose‐response association between a cumulative count of opium use and lung cancer risk. The OR for regular opium use was higher for small cell carcinoma than in other histology (8.3, 95% CI: 4.8, 14.4). The OR of developing lung cancer among opium users was higher in females (7.4, 95% CI: 3.8, 14.5) than in males (3.3, 95% CI: 2.6, 4.2). The OR for users of both opium and tobacco was 13.4 (95% CI: 10.2, 17.7) compared to nonusers of anything. The risk of developing lung cancer is higher in regular opium users, and these results strengthen the conclusions on the carcinogenicity of opium. The association is stronger for small cell carcinoma cases than in other histology. Abstract : What's new? Opium was recently classified as a carcinogen by the IARC. In this multicenter case‐control study on the association between opium use and risk of lung cancer the authors showed a decreasing risk of lung cancer after opium cessation. There was a higher association among small cell carcinoma type than others. The association was highly significant among never tobacco users, too, and there was an additive interaction between tobacco and opium use. The evidence is in line with the carcinogenicity of opium use.